ANALISIS SISTEM PEMBAYARAN CASH ON DELIVERY (COD) DALAM BERBELANJA ONLINE DI SHOPEE MENURUT PERSPEKTIF FIQH MUAMALAH - Rahmadhania, Laila Suci; Romadhoni, Serli; Arimustofa, Daniel Nurfatra; Wulandari, Niken; Hanifah, Ummu; Waluyo, Waluyo (JISEF : Journal Of International Sharia Economics And Financial, 2024)
Shopee is an application feature whose function is to provide information on online sales of products. The payment method that is most popular with MarketPalce Shoppe users is the cash on delivery (COD) payment method which is easy and uncomplicated. The aim of this research is to find out the implementation of buying and selling using the cash on delivery (COD) method on the Shopee marketplace and to find out what the Islamic jurisprudence perspective is in buying and selling using the cash on delivery (COD) method on the Shopee marketplace. This research method is a literacy method to determine the analysis of the cash on delivery (COD) payment system in online shopping at Shopee according to the muamalah fiqh perspective and uses qualitative research derived from interview scripts and based on in-depth journals with several consumers. The results of the research are that online transactions are in accordance with muamalah fiqh, the use of the contract is the greeting contract. This is because people order by providing the characteristics of an object to be purchased, while the seller has provided a detailed description of the item.